PERGESERAN MAKNA MOTIF BATIK YOGYAKARTA – SURAKARTA - Doddy Wihardi; Riyodina G.Pratikto; Shinta Kristanty (Jurnal Ilmiah Komunikasi Makna, 2015)
Recognition the world to batik as the world cultural heritage belonging to Indonesia by UNESCO increase popularity batik. But the increase was not in balance to understanding of meaning philosophical in any motive batik, for example the use of batik by the community not in accordance with the designation on motive that is. Research aims to understand shift the meaning of elements batik Yogyakarta-Surakarta. Research questions submitted is how shift meaning on motive batik Yogyakarta-Surakarta? Research methodology used is analysis logician Roland Barthes. An object used in this research was batik Yogyakarta-Surakarta. Data obtained from observation to a batik Yogyakarta-Surakarta traditional and contemporary, book, journal, interview as well as from sources online. Output from the study will make a journal and a recommendations for institutions associated with the development of batik like: the government, Batik entrepreneurs and consumers.Key words: Batik, meaning, motif